2017
DOI: 10.1177/2325967117708286
|View full text |Cite
|
Sign up to set email alerts
|

Orthopaedic Resident Preparation and Confidence in Treating On-Field Injuries

Abstract: Background:Orthopaedic surgery residents may cover athletic events, although the training provided to prepare residents for this role and oversight from attending physicians during these activities is not well understood.Purpose:To survey orthopaedic residents about the training provided by their residency program for on-field athletic coverage and to understand their levels of preparation for this role and confidence in treating commonly encountered on-field conditions.Study Design:Descriptive epidemiology st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 23 publications
1
8
1
Order By: Relevance
“…12 Unfortunately, a surprisingly high number of programs reported a lack of oversight by attending physicians during resident event coverage. This is similar to a survey of residents by Hodax et al 5 who found that 32% of programs had direct attending supervision at all events and 39% had variable supervision by attending surgeons. Supervision and mentorship by attending surgeons may be particularly valuable in role modeling sideline evaluation and medical professionalism in the community setting.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…12 Unfortunately, a surprisingly high number of programs reported a lack of oversight by attending physicians during resident event coverage. This is similar to a survey of residents by Hodax et al 5 who found that 32% of programs had direct attending supervision at all events and 39% had variable supervision by attending surgeons. Supervision and mentorship by attending surgeons may be particularly valuable in role modeling sideline evaluation and medical professionalism in the community setting.…”
Section: Discussionsupporting
confidence: 88%
“…[1][2][3][4] Orthopaedic surgeons are frequently called on to serve as medical personnel for organized youth, adolescent, collegiate, and professional sporting events. [5][6][7] The pathology that a team physician may encounter during athletic events includes a broad array of medical, dental, ophthalmic, neurologic, and musculoskeletal conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many orthopaedic surgeons serve on the sidelines during sporting events to render medical care to the injured athlete as needed. Whilst most orthopaedic surgeons are comfortable managing musculoskeletal injuries (which are involved in over 70% of on-field evaluations), these are not the only medical emergencies that occur [18] .…”
mentioning
confidence: 99%
“…A 2017 study of orthopaedic residents acting as team physicians showed that whilst residents’ confidence in managing musculoskeletal sideline injuries grew consistently over the five years of their training, their confidence in managing other serious on-field medical emergencies such as commotio cordis, concussion, dehydration, heat injury, and ocular injury did not [18] . The conclusion of this study was that the provision of additional training for these physicians was the most desirable solution [18] .…”
mentioning
confidence: 99%